Analysis of P ® film-coated caplet quality control by implementing statistical process control method at PT. YF - Oktavia Eka Puspita; Achmad Fudholi (Indonesian Journal of Pharmacy, 2011)
Manufacturing of film-coated caplet  dosage form is a multi-steps  process, including  weighing,  blending,  granulating,  drying,  compression,  coating,  and packaging.  Every  manufacturing  process  is  influenced  by  natural  variation  and assignable  variation  which  caused  the  process  operates  out-of  control  and interfering  consistency  and  attainment  of  output  quality  specification.  Based  on the above background a research was conducted upon manufacturing process of P® film  coated  caplet  at  PT.YF.  This  research  was  limited  for  core  caplet compression step and film coating step instead of entire production process. The purposes  of  this  research  were  analyzing  core  caplet  compression  process  and coating process and measuring process capabilityof those steps in meeting the pre-determined  quality  specifications.  Investigation  of  20  latest  consecutive batch  record  documents  within  2009  period  was  conducted  in  collecting quantitative data measurement of caplet quality characteristics including weight uniformity,  hardness,  friability,  disintegration,and  dissolution  of  drug  substance of  P® film  coated  caplet.  Those  data  were  analyzed  using control  chart  SPC method and process capabilitywas measured by Cpk index. The results showed that  from  caplet  core  compression  step  the  control  chart  of  caplet  weight uniformity  and   friability  indicates    statistically  in-control,  meanwhile  step  the control  chart  of  hardness;  disintegration  time  and  dissolution  of  Paracetamol  ; Ibuprophen indicates statistically out-of control. The result of film coating step of  P® film-coated  caplet  showed  that  the  control  chart  of weight  uniformity; hardness  and  Ibuprophen  dissolution  indicates    statistically  out-of  control, meanwhile  disintegration  time  and  Paracetamol  dissolution  was  statistically  in control.  The  process  capability  index,  Cpk.  of  core caplet  weight  uniformity: 1.375, and Paracetamol P® film-coated caplet dissolution: 1,841,Key  words  : Natural  variation,  assignable  variation,  Statistical  Process  Control,  P® filmcoated caplet